Unparalleled mitochondrial heteroplasmy and Wolbachia co-infection in the non-model bee, Amphylaeus morosus - Olivia K. Davies; James B. Dorey; Mark I. Stevens; Michael G. Gardner; Tessa M. Bradford; Michael P. Schwarz (Current Research in Insect Science, 2022)
Mitochondrial heteroplasmy is the occurrence of more than one type of mitochondrial DNA within a single individual. Although generally reported to occur in a small subset of individuals within a species, there are some instances of widespread heteroplasmy across entire populations. Amphylaeus morosus is an Australian native bee species in the diverse and cosmopolitan bee family Colletidae. This species has an extensive geographical range along the eastern Australian coast, from southern Queensland to western Victoria, covering approximately 2,000 km. Seventy individuals were collected from five localities across this geographical range and sequenced using Sanger sequencing for the mitochondrial cytochrome c oxidase subunit I (COI) gene. These data indicate that every individual had the same consistent heteroplasmic sites but no other nucleotide variation, suggesting two conserved and widespread heteroplasmic mitogenomes. Ion Torrent shotgun sequencing revealed that heteroplasmy occurred across multiple mitochondrial protein-coding genes and is unlikely explained by transposition of mitochondrial genes into the nuclear genome (NUMTs). DNA sequence data also demonstrated a consistent co-infection of Wolbachia across the A. morosus distribution with every individual infected with both bacterial strains. Our data are consistent with the presence of two mitogenomes within all individuals examined in this species and suggest a major divergence from standard patterns of mitochondrial inheritance. Because the host's mitogenome and the Wolbachia genome are genetically linked through maternal inheritance, we propose three possible hypotheses that could explain maintenance of the widespread and conserved co-occurring bacterial and mitochondrial genomes in this species.